Uji Efek Penghambatan Enzim Xantin Oxidase Kombinasi Ekstrak Daun Kumis Kucing (Orthosiphon aristatus L.) dan Daun Sidaguri (Sida rhombifolia L.) - Nitya Nurul Fadilah (Jurnal Farmasi Indonesia, 2021)
Hyperuricemia is a high level of uric acid in the blood and can cause gout. One of the drugs used to treat hyperuricemia is allopurinol with a mechanism of inhibiting the activity of xanthine oxidase (XO). The use of these drugs can cause various side effects if used for a long period of time. Sidaguri and kumis kucing plants are known to contain flavonoids and are proven to treat gout with each plant can reduce uric acid levels in the blood and increase its excretion in urine. This study was carried out to test the combination of sidaguri and kumis kucing extracts with certain ratios in inhibiting the activity of the xanthine oxidase enzyme. In this study, a combination of extracts was made using maceration method. The inhibition of xanthine oxidase activity by ethanol extract in vitro was determined by decreasing the production of uric acid monitored with a spectrophotometer at (λ) 292nm with xanthine as a substrate. Then determined the best IC50. As a comparison allopurinol is used. Based on the results of in vitro tests, the best comparison of the combination of kumis kucing extract and sidaguri extract can inhibit the activity of XO enzymes with the best IC50 in a row is the combination of kumis kucing and sidaguri extracts 1:1 (20.99ppm), 1:2 (39.64ppm), and 1:0.5 (52.28ppm).